2013
DOI: 10.4304/jcp.8.5.1255-1266
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Conception of Learning Problems of Students by Combining the Misconception Domain and Structural Analysis Methods

Abstract: The purpose of this paper was to analyze the structure of difficult concepts learning within the classroom. The sample of the study was 18 fourth grade students in Central Taiwan, and the exam tools were produced by teachers for math exams. In this paper, a combination of the Rasch Model GSP chart analysis theory, the misconception domain, the Interpretive Structural Modeling (ISM) and Grey Structural Model (GSM) was used. The results are as follows: (1) Based on the change in students' average grade and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Hassnert and Allwood studied user error experimental analysis with two self-registration software products [18][19]. The experimental results showed that there was no common error classification criterion [20][21], indicating that other classification methods were not applicable. It is necessary to classify and summarize user errors according to specific experimental analysis.…”
Section: Research Methods Of User Error Classificationmentioning
confidence: 99%
“…Hassnert and Allwood studied user error experimental analysis with two self-registration software products [18][19]. The experimental results showed that there was no common error classification criterion [20][21], indicating that other classification methods were not applicable. It is necessary to classify and summarize user errors according to specific experimental analysis.…”
Section: Research Methods Of User Error Classificationmentioning
confidence: 99%
“…Secondly, other agent's strategy should be considered for strategies selection of learning agent in MAS, the changes from current state to next state aren't all decided by actions of learning agent, other agents also choose actions which change system state, the uncertainty of successor function is caused by unknown of other agent's strategy [5] [6]. In most cases, the other agent's behavior is not random, but can be considered as action strategy of probability distribution, which is random behavior that is subject to a certain probability distribution in a certain state.…”
Section: Introductionmentioning
confidence: 99%